An independent character of students in learning during the pandemic - Nurazizah, Reni (ETUDE: Journal of Educational Research, 2021)
Background: Â Online learning is carried out as the right step to prevent the transmission of the Covid-19 virus so that students will not miss lessons as planned in the curriculum for one academic year. When students learn at home following online learning provided by the teachers, parents are not always present to accompany and monitor the learning process of students, so inevitably independent learning is needed so that students can participate in learning activities and be responsible for complete the task of learning each subject. Teachers and parents must work together to supervise and encourage students to be able to learn independently.Purpose: The purpose of this study was to determine the extent to which elementary school students' independent character during distance learning as a result of the COVID-19 pandemic.Design and methods: This type of research is descriptive qualitative research. The subjects of this study were homeroom teachers and teachers of sports subjects. The data validation technique of this research is the source triangulation validation technique.Results: The existence of good examples and cooperation between teachers and parents will help students to be able to imitate and do so, so that awareness and habits will be formed in students to become humans who are full of responsibility with their duties. From the online learning process that is currently being carried out, it is hoped that the teacher is not satisfied with providing material through one learning application that is commonly used, especially in elementary schools, which is only through the WhatsApp application, the teacher can provide learning materials by making learning videos that are easy for students to understand. By considering the number/portion given, so as to minimize the stress level of students, especially by giving assignments that are always given every day.